2021
DOI: 10.3390/ijms22105272
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypobaric Hypoxic Preconditioning Provides Neuroprotection by Increasing Antioxidant Activity, Erythropoietin Expression and Preventing Apoptosis and Astrogliosis in the Brain of Adult Rats Exposed to Acute Severe Hypoxia

Abstract: Background: Exposure to intermittent hypoxia has been demonstrated to be an efficient tool for hypoxic preconditioning, preventing damage to cells and demonstrating therapeutic benefits. We aimed to evaluate the effects of respiratory intermittent hypobaric hypoxia (IHH) to avoid brain injury caused by exposure to acute severe hypoxia (ASH). Methods: biomarkers of oxidative damage, mitochondrial apoptosis, and transcriptional factors in response to hypoxia were assessed by Western blot and immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Moderate hypoxia (3,500–5,500 m) ( 27 ) is a feasible, economical, and effective non-invasive method of preconditioning that may enhance tissue tolerance through moderate stimulation aimed at achieving tissue protection. Numerous basic research efforts have demonstrated the neuroprotective effect of hypoxic preconditioning (HPC) from various perspectives ( 28 31 ). Intermittent hypobaric hypoxia was reported to improve vasodilation ( 32 ), reduce vascular sclerosis, increase left ventricular ejection fraction, and upregulate the expression of antioxidant enzymes in cardiac tissues ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate hypoxia (3,500–5,500 m) ( 27 ) is a feasible, economical, and effective non-invasive method of preconditioning that may enhance tissue tolerance through moderate stimulation aimed at achieving tissue protection. Numerous basic research efforts have demonstrated the neuroprotective effect of hypoxic preconditioning (HPC) from various perspectives ( 28 31 ). Intermittent hypobaric hypoxia was reported to improve vasodilation ( 32 ), reduce vascular sclerosis, increase left ventricular ejection fraction, and upregulate the expression of antioxidant enzymes in cardiac tissues ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the upregulation of heat shock protein 70 may play a pivotal role in tissue tolerance during the hypobaric hypoxia procedure ( 34 , 35 ). Activation of hypoxia-inducible factor and its downstream target genes, including glucose transporters, vascular endothelial growth factor b, and erythropoietin, has also been demonstrated to contribute to HPC-induced ischemic tolerance ( 28 , 36 ). Hypoxic preconditioned neural stem cells improve the efficacy of stem cell therapy in brain injury ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies, rat brains subjected to acute hypoxia exhibited increased cytochrome c and caspase 3. In contrast, when acute hypoxia was preceded by HP, no differences were found in these markers compared to normoxic rats (Coimbra-Costa et al 2021) suggesting that HP may prevent mitochondrial dysfunction and apoptosis.…”
Section: Enhanced Neuronal Cell Survivalmentioning
confidence: 75%
“…This antioxidant response decreases the activity of pro-apoptotic cascades mediated by the downregulation of nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) and the upregulation of erythropoietin (EPO) highlighting the neuroprotective effect of HP. Furthermore, sublethal hypoxic conditions stimulate neurogenesis and angiogenesis similar to what occurs during embryonic brain development (Coimbra-Costa et al 2021). Thus, the neuroprotective mechanisms triggered by HP include activation of antioxidant and anti-apoptotic pathways, suppression of excitotoxicity, promotion of cell proliferation, activation of anti-inflammatory responses, and enhancement of vascular regulation (Fan et al 2020) (Fig.…”
Section: Oxidative Stressmentioning
confidence: 96%